Safety and immunogenicity of inactivated SARS-CoV-2 vaccines in people with gastrointestinal cancer. (September 2022) - Li, Tong; Song, Rui; Wang, Jingjie; Zhang, Jianbo; Cai, Hongxing; He, Hongmei; Hu, Wei; Yu, Dajun; Wang, Chuanhu; Pan, Qingbo; Peng, Mingli; Ren, Hong; et al.
Highlights: Inactivated COVID-19 vaccine was safe but with lower immunogenicity for Gastrointestinal cancer. The frequency of total memory B cells (MBCs) between GI cancer and healthy people did not differ. Activated MBCs and resting MBCs decreased, and intermediate MBCs and atypical MBCs increased for GI cancer. Abstract: Objectives: This study aimed to evaluate the safety and immunogenicity of inactivated COVID-19 vaccines in patients with gastrointestinal cancer (GI) cancer. The role of memory B cells (MBCs) in the humoral response to COVID-19 vaccination was also investigated. Methods: In this prospective observational study, GI cancer patients and healthy individuals who had received 2 doses of inactivated COVID-19 vaccines were included. The data regarding adverse effects, serum anti-receptor binding domain (RBD)-IgG, neutralizing antibodies (NAbs), and frequencies of MBCs were collected prospectively. Results: The inactivated COVID-19 vaccines were safe and well tolerated. Serum anti-RBG-IgG and NAbs were lower for cancer patients. Old age, high ASA score, and receiving active chemotherapy were risk factors for lower antibody titers. The frequencies of activated and resting MBCs decreased in (17.45% vs 38.11%, P = 0.002; 16.98% vs 34.13%, P = 0.023), while the frequencies of intermediate and atypical MBCs increased in cancer patients (40.06% vs 19.87%, P = 0.010; 25.47% vs 16.61%, P = 0.025). The serum antibody titer decreased gradually during follow-up but increased when a booster vaccine was given. Conclusion: The inactivated COVID-19 vaccines were well tolerated in patients with GI cancer but with lower immunogenicity. The subpopulations of MBCs were disordered in cancer patients, and a booster vaccine may be prioritized for them.